Communication, socialization, and ITC. The psychosocial construction of sustainability - Pol, Enric; Castrechini-Trotta, Angela; Pellicer-Cardona, Isabel; Cañete-Massé, Cristina (Frontiers in Psychology, 2024)
Over the past two decades, the facets related to environmental crises (in the plural) have grown increasingly intricate. What began as environmentalists’ apprehension over nature degradation and the encouragement of citizen-driven initiatives has evolved. The current shift in emphasis and prevailing message strives to foster a culture where citizens refrain from independent initiatives. Instead, the directive is to heed the guidance of the knowledgeable (scientists, politicians, corporations, interest groups, etc.), as substantiated by our investigative findings, which align, in part, with existing literature. Conversely, our exploration into environmental communication, notably the insights gleaned from longitudinal research concerning pro-environmental knowledge, attitudes, and actions, reveals a decline in citizens’ effective inclinations toward embracing pro-environmental behaviours. Meanwhile, the escalation of the climate crisis is fueling heightened levels of echo-anxiety and solastalgia. This trajectory is closely intertwined with a growing global disillusionment within society – not just regarding the future – instilling a sense of disillusionment concerning pro-environmental messages and slogans disseminated by governing bodies and corporations. This has led to a state resembling learned helplessness, as articulated by Seligman, or what we prefer to term “induced” helplessness, rather than fostering conditions conducive to empowerment. This article comprehensively examines various reports and our inquiries, revealing how communication management and its constituents lie at the heart of forging novel narratives, fresh cognitive dissonances, and emerging social representations. Notably emphasised is the pivotal role played by information and communication technologies (ICT), particularly through dissemination on widely-used social networks. Since the 2010s, these platforms have assumed a paramount role in shaping socialisation processes, surpassing educational institutions and conventional mass media.